The Enigmatic Functional Role of Thymus Gland in Fighting Against SARS- CoV- 2 and COVID- 19 - Literature Review - AL- Ruwishan, Aiman; Nasr, Basma; Gamallat, Yaser; Maher, Kassem (Journal of medical and pharmaceutical sciences, 2020)
Background and Objective: Coronavirus disease 2019 (COVID- 19) caused a world pandemic, spreading rampantly throughout the world. Although people of all ages were infected, there was an obvious partiality in terms of the disease severity follow infection in children patients’ group of age. Consequently, in order to achieve a better understanding of the discriminative behavior of the Severe Acute Respiratory Syndrome Coronavirus 2 (SARS- CoV- 2) aggressiveness throughout all different groups of age, thus, the main potential aims of this review were not only to give a new impetus toward the unintentional omission of the effective immune role of the thymus gland in children on tackling COVID- 19, but also to discuss the potential possibility of thymosin replacement therapy utilization in the form of thymosin alpha 1, as a key booster in fighting against COVID- 19.Method: A literature search of COVID- 19 and SARS- CoV2 related published articles and literatures using science search engines encompassing PubMed, Medline and Google Scholar.Results: The main result of this review had exhibited low possibility of SARS- CoV- 2 infection, far less reported lymphopenia as well as low exposure rate to opportunistic complications of COVID- 19 in children, compared to adults and elderly individuals. Therefore, this discrepancies in infection rates and laboratory findings may potentially indicate the paramount importance of fully functioned thymus gland in fighting against SARS- CoV- 2 infection in children.Conclusion and Recommendations: COVID- 19 remains a global dilemma causing massive devastation on all aspects of social and economic life. Due to the discriminative behavior of SARS- CoV- 2 aggressiveness throughout all different groups of age detected through this literature review. Hence, more research and clinical trials on thymosin alpha- 1 efficacy are needed in order to understand the possible role of the thymus gland in protecting against SARS- CoV- 2 infection and minimizing COVID- 19 symptoms and complications.
Keywords: Covid-19; SARS-CoV-2; lymphocytopenia; thymus gland; thymosin alpha-1